2019
DOI: 10.1101/635631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable Species Boundaries Despite Ten Million Years of Hybridization in Tropical Eels

Abstract: 1Genomic evidence is increasingly underpinning that hybridization between taxa is commonplace, 2 challenging our views on the mechanisms that maintain their boundaries. Here, we focus on seven 3 catadromous eel species (genus Anguilla), and use genome-wide sequence data from more than 450 4 individuals sampled across the tropical Indo-Pacific, morphological information, and three newly 5 assembled draft genomes to compare contemporary patterns of hybridization with signatures of 6 past gene flow across a time-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 116 publications
1
20
0
Order By: Relevance
“…However, the domestic genetic material moving into CSB does not imply that the CSB faces a genetic extinction threat as these segmentations are rarely fixed in CSB (Tables S5 and S7). The deleterious alleles that are introduce from domesticated ducks will possibly be eliminated by purifying selection (Juric et al 2016;Barth et al 2020). It is noteworthy that continuous and abundant release of domesticated animals greatly increases the chance of wild-domesticated hybridization and even backcrossing into their wild parental population, which may result in the genetic swamping of wild populations (Chazara et al, 2010;Lavretsky et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the domestic genetic material moving into CSB does not imply that the CSB faces a genetic extinction threat as these segmentations are rarely fixed in CSB (Tables S5 and S7). The deleterious alleles that are introduce from domesticated ducks will possibly be eliminated by purifying selection (Juric et al 2016;Barth et al 2020). It is noteworthy that continuous and abundant release of domesticated animals greatly increases the chance of wild-domesticated hybridization and even backcrossing into their wild parental population, which may result in the genetic swamping of wild populations (Chazara et al, 2010;Lavretsky et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent study indicated that hybridization and gene exchange are pervasive in tropical eel species, but that these species have nevertheless remained distinct entities for several million years. Cytonuclear incompatibilities and hybrid breakdown may be powerful mechanisms which help maintaining species boundaries [49].…”
Section: Discussionmentioning
confidence: 99%
“…These authors contend that species delimitations from multiple herpetological studies were unfounded because they represent arbitrary slices of clines or conjecture that hybrid zones are too wide for species to be valid. However, they ignore that hybridization across the tree of life is common, these species diverged during the Pleistocene or even earlier and have maintained independent evolutionary trajectories, and incomplete gene (lineage) sorting is one expectation of the speciation process (Wiley, 1978;Knowles and Carstens, 2007b;de Queiroz, 2007;Payseur and Rieseberg, 2016;Gompert et al, 2017;Barth et al, 2020;Moran et al, 2021).…”
Section: Controversial Species Delimitations In Herpetologymentioning
confidence: 99%